2017
DOI: 10.1002/pmic.201600427
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles in the Adaptive Process of Prostate Cancer during Inhibition of Androgen Receptor Signaling by Enzalutamide

Abstract: Current treatments for advanced prostate cancer focus on inhibition of the androgen receptor (AR) by androgen deprivation therapy (ADT). However, complex interactions mediated by tumor suppressors, oncogenes, aberrations of AR expression, or de novo androgen production have been shown to induce the adaptive response of prostate cancer, leading to the development of castration resistant prostate cancer. In this study, we report the effects of AR antagonist, enzalutamide on the protein contents of extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Soekmadji et al recently demonstrated that exposure of LNCaP and DUCaP to dihydrotestosterone (DHT) increased the secretion of CD9-expressing exosomes (without any increase in the total number of secreted exosomes) ( 137 ). Proteomic analyses showed that DHT treatment, culture in androgen-free medium and treatment with the antiandrogen enzalutamide are effectively able to modify exosomes contents ( 137 , 138 ). When CD9-enriched exosomes obtained after DHT treatment were inserted in the culture media of androgen-deprived LNCaP cells, an increased proliferation was observed.…”
Section: Biological Functions Of Exosomes In Prostate Cancermentioning
confidence: 99%
“…Soekmadji et al recently demonstrated that exposure of LNCaP and DUCaP to dihydrotestosterone (DHT) increased the secretion of CD9-expressing exosomes (without any increase in the total number of secreted exosomes) ( 137 ). Proteomic analyses showed that DHT treatment, culture in androgen-free medium and treatment with the antiandrogen enzalutamide are effectively able to modify exosomes contents ( 137 , 138 ). When CD9-enriched exosomes obtained after DHT treatment were inserted in the culture media of androgen-deprived LNCaP cells, an increased proliferation was observed.…”
Section: Biological Functions Of Exosomes In Prostate Cancermentioning
confidence: 99%
“…Plasma membrane Ca 2+ -ATPases (PMCAs) are calcium pumps that use ATP hydrolysis to push calcium from the cytosol into the extracellular milieu. PMCA1 has been identified as a protein that is regulated by the AR in PCa LNCaP cells [103]. Increased secretion of PMCA1 in extracellular vesicles has been associated with inhibition of the AR by the AR antagonist enzalutamide [103].…”
Section: Calcium Pumps and Cation Permeable Channelsmentioning
confidence: 99%
“…For advanced PCa, current treatments focus on inhibition of the androgen receptor. Soekmadji et al [38] (Table 1) investigated EV's protein cargo in supernatant of prostate cancer cells after incubation with enzalutamide. The 34 vesicular proteins were described altered by the androgen receptor antagonist.…”
Section: Evs In Prostate Cancermentioning
confidence: 99%
“…The 34 vesicular proteins were described altered by the androgen receptor antagonist. Especially the plasma membrane calcium pump, ATP2B1/PMCA ATPase, was identified as a part of the cross-talk of androgen receptor signaling and EV pathways in mediating resistance towards hormone therapy [38].…”
Section: Evs In Prostate Cancermentioning
confidence: 99%